2008
DOI: 10.1002/ps.1612
|View full text |Cite
|
Sign up to set email alerts
|

Rate, placement and timing of aldicarb applications to control Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Psyllidae), in oranges

Abstract: Aldicarb application at 5.6 kg ha(-1) to the bed side of mature citrus trees 2-3 months before spring growth can suppress ACP through spring without a direct effect on principal psyllid natural enemies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 17 publications
0
29
1
Order By: Relevance
“…We did not observe this species in citrus groves during several of our studies through 2008, nor have we found any reports of its appearance in Florida citrus in response to the recent invasions of T. citricida and D. citri (Qureshi and Stansly 2008, 2010. This species was not cited as a predator of D. citri by Michaud (2004) although it earlier was included as a minor element of the coccinellid fauna observed on Florida citrus (Michaud 2000).…”
contrasting
confidence: 46%
“…We did not observe this species in citrus groves during several of our studies through 2008, nor have we found any reports of its appearance in Florida citrus in response to the recent invasions of T. citricida and D. citri (Qureshi and Stansly 2008, 2010. This species was not cited as a predator of D. citri by Michaud (2004) although it earlier was included as a minor element of the coccinellid fauna observed on Florida citrus (Michaud 2000).…”
contrasting
confidence: 46%
“…Furthermore, soil application of neonicotinoids, especially imidacloprid, is not recommended for mature trees, as application at full labeled rate did not result in concentrations that killed feeding ACP . Mature trees produce a major flush in late winter and early spring, followed by minor flushes in early summer, late summer and fall, with ACP populations reaching peak numbers during these flushing periods . Therefore, foliar applications with broad‐spectrum insecticides during late winter to mature trees, when few overwintering adults are the only survivors, exhibited a profound effect on ACP populations for a longer period .…”
Section: Chemical Control Of Acpmentioning
confidence: 99%
“…Although soil applications are supplemented with foliar treatments of broad‐spectrum insecticides, soil‐applied systemic insecticides do not exhibit the quick knockdown effect on ACP exerted by foliar applied broad‐spectrum insecticides. Systemic insecticides can be applied to soil by soil drench, chemigation (through drip irrigation) or spot application at bed/swale side or to tree trunk (trunk application, trunk paint and trunk injection) . Soil application methods are widely followed in the United States, while tree trunk application methods are usually followed in other citrus‐growing countries of the world (India and Vietnam).…”
Section: Chemical Control Of Acpmentioning
confidence: 99%
“…Integrated control based on natural enemies, bio-rational materials, chemicals, and cultural practices could be the most acceptable pest management tactics (Yang et al 2006;JuanBlasco et al 2012). Natural enemies of D. citri include predators such as ladybeetles (Coleoptera: Coccinellidae), lacewings (Neuroptera: Chrysopidae), spiders (Aranae), and hoverflies (Diptera: Syrphidae), parasitoids such as Diaphorencyrtis aligarhensis (Shafee, Alam & Agaral) (Hymenoptera: Encyrtidae) and Tamarixia radiata (Waterston) (Hymenoptera: Eulophidae), and certain entomopathogens (Aubert & Quilici 1984;Hoy & Nguyen 2001;Michaud 2002Michaud , 2004Pluke et al 2005;Yang et al 2006;Qureshi & Stansly 2008, 2009). However, any single tactic use alone is unlikely to provide sufficient suppression of D. citri populations, so that more proactive and augmentative approaches to biological control should be developed (Juan-Blasco et al 2012).…”
Section: Introductionmentioning
confidence: 99%